Supporting students with disabilities: discrepancies in educational outcomes and the need for comprehensive postsecondary support - Melissa Beck Wells (Discover Education)
Abstract Students with disabilities (SWDs) continue to face significant barriers in postsecondary education, despite federal mandates such as IDEA, ADA, and Section 504. This study explores the role of Universal Design for Learning (UDL) and systemic transition support in mitigating disparities in enrollment, retention, and degree completion for SWDs. Using recent datasets and a structured literature synthesis, the research illustrates how gaps in institutional practices, faculty preparedness, and interagency coordination affect SWDs’ outcomes. Data visualizations demonstrate that while enrollment has improved modestly, employment and completion rates remain disproportionately low for students with disabilities, particularly those with intersectional identities. The findings suggest a shift from reactive accommodation toward proactive inclusive design is essential. Recommendations include federal and state policy alignment, mandatory UDL training, and integrated transition services that begin before college entry. Limitations include the constraints of secondary data and institutional variability across states. Implications for future research and policy reform are discussed.